Increased epinephrine and skeletal muscle responses to hypoglycemia in non-insulin-dependent diabetes mellitus. - Shamoon, H (1994)
We evaluated skeletal muscle counterregulation during hypoglycemia in nine subjects with non-insulin-dependent diabetes mellitus (NIDDM) (HbA1c 9.4 +/- 0.5%, nl < 6.2%) compared with six normal controls, matched for age (51 +/- 3 and 49 +/- 5 yr, respectively) and body mass index (27.3 +/- 1.2 and 27.0 +/- 2.1 kg/m2). After 60 min of euglycemia (plasma insulin approximately 140 microU/ml), plasma glucose was lowered to 62 +/- 2 mg/dl by 120 min. Hypoglycemia induced a 2.2-fold greater increase in plasma epinephrine in NIDDM (P < 0.001), while the plasma glucagon response was blunted (P < 0.01). Hepatic glucose output ([3H-3]glucose) suppressed similarly during euglycemia, but during hypoglycemia was greater in NIDDM (P < 0.005). Conversely, glucose uptake during euglycemia was 150% greater in controls (P < 0.01) and remained persistently higher than in NIDDM during hypoglycemia. In NIDDM, plasma FFA concentrations were approximately fivefold greater (P < 0.001), and plasma lactate levels were approximately 40% higher than in controls during hypoglycemia (P < 0.01); the rates of glycolysis from plasma glucose were similar in the two groups despite a 49% lower rate of glucose uptake in NIDDM (3.4 +/- 0.9 vs. 6.9 +/- 1.3 mg/kg per minute, P < 0.001). Muscle glycogen synthase activity fell by 42% with hypoglycemia (P < 0.01) in NIDDM but not in controls. In addition, glycogen phosphorylase was activated by 56% during hypoglycemia in NIDDM only (P < 0.01). Muscle glucose-6-phosphate concentrations rose during hypoglycemia by a twofold greater increment in NIDDM (P < 0.01). Thus, skeletal muscle participates in hypoglycemia counterregulation in NIDDM, directly by decreased removal of plasma glucose and, indirectly, by providing lactate for hepatic gluconeogenesis. Consequently, in addition to inherent insulin resistance in NIDDM, the enhanced plasma epinephrine response during hypoglycemia may partially offset impaired glucagon secretion and counteract the effects of hyperinsulinemia on liver, fat, and skeletal muscle.